Waqf Banking Products for Financial Inclusion in Malaysia - Mohd Asyraf Yusof
The combination of Waqf institutions and Islamic banking institutions has proven to catalyze Islamic economic development. Apart from that, these combinations can also address Malaysia's financial inclusion problem. Financial inclusion is defined as the availability and equality of opportunities to access financial services. It refers to how individuals and businesses can access appropriate, affordable, and timely financial products and services. These include banking, financing, equity, and takaful products. In recent years, there has been a massive gap in scientific research studying the involvement of waqf institutions, especially in addressing the financial inclusion problem. In particular, the innovation and use of cash waqf in waqf institutions are minimal. It will cause a slowdown in the development of the Islamic economy. Thus, the contribution of waqf institutions to addressing financial inclusion in the academic world is limited. For these reasons, this study proposes waqf banking products to address the issue of financial inclusion and fill the gap. This study uses a qualitative approach with an exploratory research design to answer research questions. The data collection methods used in this study are a semi-structured interview and a focus group interview. The researcher has sent the invitation for research interview sessions to all waqf organizations, available Islamic banking institutions, microfinance institutions in Malaysia, and Muslim scholars for data collection. Unfortunately, only a few of them agreed to be interviewed. This study tries to answer research questions such as what waqf banking products are, how waqf banking products can be created, who will benefit from waqf banking products, and where, why, and when waqf banking products need to be made. The findings of this study show that the development of waqf banking products could address the financial inclusion problem faced by Malaysians and thus help B40 survive in this post-pandemic Coronavirus Disease 2019 (COVID-19) era. Although there were challenges in attempting to adopt waqf banking products, such as the rules and regulations of waqf and banking, governance, and human resources, the findings of this study could be a reference for bankers, policymakers, and waqf organizations to develop waqf banking products in Malaysia.